The self-care practices of school principals. Issue 4 (26th June 2020) - Ray, Joshua; Pijanowski, John; Lasater, Kara
Abstract : Purpose: The purpose of this study was to explore the well-being of school principals and the job-embedded demands responsible for challenging their adoption of healthy self-care practices. Design/methodology/approach: Drawing upon a multidisciplinary theoretical framework that included contributions from the fields of neurobiology and psychology, three tiers of self-care needs were established to inform the study: basic physiological needs such as sleep, hydration, and nutrition; active self-care practices such as exercise, relaxation, and stress relief; and higher order needs such as belongingness and love addressed through work-life balance, volunteerism, and relational belonging. A 45-question survey containing Likert scale items and open-ended questions was returned from 473 practicing building administrators (a 24.4% response rate). Findings: Findings from this study, compared to estimates from the literature, indicate that school leaders work longer hours, are more sleep deprived, more dehydrated, have poorer diet practices, exercise less regularly, and spend less time with their friends and family than the general population. Administrators struggled to find ways within their control to improve their self-care behavior and offered suggestions regarding how the structure of the job itself might be changed to facilitate improving the health of school leaders. Originality/value: This work offers insight into the current well-being of school principals, and by better understanding administrators' self-care practices, this study can inform the field in developing supports, practices, and expectations, which promote the health and well-being of building-level leaders. Unhealthy self-care practices may influence their effectiveness, happiness, and possibly their longevity within the profession. Data collected through this study informed ideas about policies and procedures that could promote greater opportunities for healthier, more effective leaders within schools.